Determination of Trace Elements in Ashes of Milk Samples by Using XRF Technique - Sogut, Omer; Bali, Tugba; Baltas, Hasan; Apaydin, Gökhan (Asian Journal of Chemistry, 2013)
Energy dispersive X-ray fluorescence system has been used to determine the heavy metal ions present in cow's milk. Samples have been collected from farm and markets within the border of Kahramanmaras province, Turkey. An Epsilon 5 PANalytical Almelo, the Netherlands model energy dispersive X-ray fluorescence spectrometer has been used to analyze the samples. As a result of analysis of the samples, the various concentrations of elements such as Na, Mg, Al, Si, P, S, Cl, K, Ca, Cr, Mn, Fe, Ni, Cu, Zn, As, Br, Rb, Sr, Y, Zr, I, Yb, Hf and Pb were found.